Cardiac phenotyping in ex vivo murine embryos using microMRI. - Cleary, J; Price, A; Thomas, D; Scambler, P; Kyriakopoulou, V; McCue, K; Schneider, J; Ordidge, R; Lythgoe, M (2009)
Microscopic MRI (microMRI) is an emerging technique for high-throughput phenotyping of transgenic mouse embryos, and is capable of visualising abnormalities in cardiac development. To identify cardiac defects in embryos, we have optimised embryo preparation and MR acquisition parameters to maximise image quality and assess the phenotypic changes in chromodomain helicase DNA-binding protein 7 (Chd7) transgenic mice. microMRI methods rely on tissue penetration with a gadolinium chelate contrast agent to reduce tissue T(1), thus improving signal-to-noise ratio (SNR) in rapid gradient echo sequences. We investigated 15.5 days post coitum (dpc) wild-type CD-1 embryos fixed in gadolinium-diethylene triamine pentaacetic acid (Gd-DTPA) solutions for either 3 days (2 and 4 mM) or 2 weeks (2, 4, 8 and 16 mM). To assess penetration of the contrast agent into heart tissue and enable image contrast simulations, T(1) and T(*) (2) were measured in heart and background agarose. Compared to 3-day, 2-week fixation showed reduced mean T(1) in the heart at both 2 and 4 mM concentrations (p < 0.0001), resulting in calculated signal gains of 23% (2 mM) and 29% (4 mM). Using T(1) and T(*) (2) values from 2-week concentrations, computer simulation of heart and background signal, and ex vivo 3D gradient echo imaging, we demonstrated that 2-week fixed embryos in 8 mM Gd-DTPA in combination with optimised parameters (TE/TR/alpha/number of averages: 9 ms/20 ms/60 degrees /7) produced the largest SNR in the heart (23.2 +/- 1.0) and heart chamber contrast-to-noise ratio (CNR) (27.1 +/- 1.6). These optimised parameters were then applied to an MRI screen of embryos heterozygous for the gene Chd7, implicated in coloboma of the eye, heart defects, atresia of the choanae, retardation of growth, genital/urinary abnormalities, ear abnormalities and deafness (CHARGE) syndrome (a condition partly characterised by cardiovascular birth defects in humans). A ventricular septal defect was readily identified in the screen, consistent with the human phenotype.